Non-Motor Symptoms of Parkinson’s Disease And Health-Related Quality Of Life: A Mini-Review - Zafari, Ali; Amiri, Parisa; Taherian, Reza (International Clinical Neuroscience Journal, 2017)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder, affecting seven million people globally. While the association of motor symptoms of PD with health-related quality of life (HRQoL) is extensively investigated, the effects of non-motor symptoms of PD, such as cognitive and behavioural symptoms, are recently highlighted. HRQoL reflects the physical, mental, and social aspects of health and is an essential subjective and reliable outcome measure of the disease. The current narrative review analyses recent literature on this topic focusing on studies in which behavioural symptoms of PD were considered as the main determinants of HRQoL.